THE EFFECT OF GIVING DATE FRUIT AT THE END OF PREGNANCY TOWARDS CERVICAL RIPENING - Rezah Andriani (Jurnal Delima Harapan, 2021)
One of the nonpharmacological therapies to trigger the performance of the oxytocin hormone for cervical ripening and acceleration of first stage labor is consuming fresh dates. Dates contain the oxytocin which can help stimulate contractions in the uterine muscles. Dates (Phoenix Dactylifera) contain carbohydrate can be directly absorbed by the body. Dates can be useful for labor, by consuming dates 60-70 grams per day at 4 weeks before giving birth to pregnant women it will be useful for cervical ripening and acceleration of first stage labor. The purpose of this study was to determine the effect of giving dates at the end of pregnancy on cervical ripening in pregnant women at PMB Ellna and Zuniawati in 2020. This study used a quantitative approach, the method was a quasi-experimental type of posttest control group design. The result the mean bishop score in the treatment group (11.1) was higher than control group (8.6). The mean duration of the first stage labor in the treatment group(231.1 minutes) was faster than control group (297.8 minutes). Statistically there was a significant difference in the bishop score and the duration of the first stage labor between the treatment group and the control group p <0.05.